MENINGKATKAN MOTIVASI BELAJAR BAHASA INGGRIS MELALUI DIGITAL STORY TELLING - REZA ANGGRIYASHATI ADARA (Interpretasi: Communication & Public Relations, 2020)
Motivation is one of the important points in learning English because motivation has a big influence on students' interest in learning English. Therefore, teachers do various things to increase student motivation. One of the things that teachers can do to increase students' interest in learning English is to use digital storytelling. In this case, digital storytelling is a storytelling process that includes various elements of technology such as audio, video, and so on. This article aims to review the benefits of using digital storytelling in learning English. In addition, this article aims to provide ideas on how teachers can incorporate digital storytelling into their English classes. With the use of digital storytelling, teachers are expected not only to increase student motivation but also to make students more independent and literate towards technology